(untitled) (Nóema, 2012)
The aim of this paper is to present a Research project on two of the most important concepts of Adlerian psychotherapeutic model (Individual Psychology) – i. e. inferiority and compensation – in an evolutionary and psychodynamic perspective. The working hypothesis is that these two concepts cross different areas (psychotherapy, philosophy, religion, mythology, history, politics, but also ethology, biology and genetics), although keeping their specificity. The Research project explores some conjectures which have been called "The basic laws of human inferiority and compensation".